2014
DOI: 10.1007/s12028-014-9995-6
|View full text |Cite
|
Sign up to set email alerts
|

The FOUR Score Predicts Mortality, Endotracheal Intubation and ICU Length of Stay After Traumatic Brain Injury

Abstract: The FOUR score was superior to the GCS in predicting in-hospital mortality in TBI patients. There was no difference between both scores in predicting unfavorable outcome, endotracheal intubation, and ICU LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 37 publications
3
54
0
6
Order By: Relevance
“…The FOUR score and the GCS score were not different in predicting unfavorable outcome (AUC 0.813 vs. 0.779, p=0.136) and endotracheal intubation (AUC 0.961 vs. 0.982, p=0.06). Both scores were good at predicting length of stay in an ICU [9]. In a recent multi-institutional study of unselected critically ill patients, the authors compared predictability of FOUR and GCS scores [17].…”
Section: Discussionmentioning
confidence: 99%
“…The FOUR score and the GCS score were not different in predicting unfavorable outcome (AUC 0.813 vs. 0.779, p=0.136) and endotracheal intubation (AUC 0.961 vs. 0.982, p=0.06). Both scores were good at predicting length of stay in an ICU [9]. In a recent multi-institutional study of unselected critically ill patients, the authors compared predictability of FOUR and GCS scores [17].…”
Section: Discussionmentioning
confidence: 99%
“…Okasha and coworkers found that the traditional GCS had similar predictive value regarding length of stay in ICU to the Full Outline of UnResponsiveness (FOUR) score. 11 It is therefore imperative to utilise any of the available scoring systems to predict likely length of stay in ICU for TBI patients as this may impact on resource allocation and outcome (see Figure 2). …”
Section: Limitationmentioning
confidence: 99%
“…Also, age affects the relationship between GCS and anatomic TBI severity, with elderly patients having better GCS scores than younger despite similar brain damage [26]. As GCS does not directly evaluate brainstem function, the full outline of unresponsiveness score, which also includes brainstem reflexes, has been validated, although its superiority to predict patient outcome when compared with GCS remains controversial [27,28]. Finally, pupillary reflex assessment could be misleading in the clinical practice; as such, pupillary reactivity tested with an infrared pupillometer was more accurate than clinical pupillary evaluation in identifying postanoxic comatose patients with poor outcome and had comparable prognostic accuracy for outcome prediction than electroencephalography (EEG) and somatosensory-evoked potential [29 & ].…”
Section: Acute Brain Injurymentioning
confidence: 99%